APOBEC3A/B deletion polymorphism and endometrial cancer risk. (16th November 2022) - Sofiyeva, Nigar; Krakstad, Camilla; Halle, Mari K.; O'Mara, Tracy A.; Romundstad, Pål; Hveem, Kristian; Vatten, Lars; Lønning, Per E.; Gansmo, Liv B.; Knappskog, Stian
Abstract: Background: A common 30 kb deletion affecting the APOBEC3A and APOBEC3B genes has been linked to increased APOBEC activity and APOBEC‐related mutational signatures in human cancers. The role of this deletion as a cancer risk factor remains controversial. Materials and Methods: We genotyped the APOBEC3A/B deletion in a sample of 1, 470 Norwegian endometrial cancer cases and compared to 1, 918 healthy controls. For assessment across Caucasian populations, we mined genotypes of the SNP rs12628403, which is in strong linkage disequilibrium with the deletion, in a GWAS dataset of 4, 274 cases and 18, 125 healthy controls, through the ECAC consortium. Results: We found the APOBEC3A/B deletion variant to be significantly associated with reduced risk of endometrial cancer among Norwegian women (OR = 0.75; 95% CI = 0.62–0.91; p = 0.003; dominant model). Similar results were found in the subgroup of endometrioid endometrial cancer (OR = 0.64; 95% CI = 0.51–0.79; p = 3.6 × 10 −5 ; dominant model). The observed risk reduction was particularly strong among individuals in the range of 50–60 years of age (OR = 0.51; 95% CI = 0.33–0.78; p = 0.002; dominant model). In the different populations included in the ECAC dataset, the ORs varied from 0.85 to 1.05. Although five out of six populations revealed ORs <1.0, the overall estimate was nonsignificant and, as such, did not formally validate the findings in the Norwegian cohort. Conclusion: The APOBEC3A/B deletion polymorphism is associated with a decreased risk of endometrial cancer in the Norwegian population. Abstract : The APOBEC3A/B deletion variant was significantly associated with reduced risk for endometrial cancer among Norwegian women. Although 5 out of 6 populations in the large ECAC data set revealed ORs <;1.0, the overall estimate was non‐significant and did not validate the findings in the Norwegian cohort.